ANALISIS MODEL E-ASESMEN BERBASIS APLIKASI SERTA PEMANFAATANNYA DALAM LAYANAN BIMBINGAN DAN KONSELING DI SEKOLAH: SYSTEMATIC LITERATURE REVIEW - Putri Rachmawati Wahyuni Asyri Ep; Rahmadani, Putri; Hartini; Sumarto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of digital technology in the era of the Industrial Revolution 4.0 has encouraged the transformation of guidance and counseling services, particularly in the implementation of digital-based student assessments (E-assessment). This study aims to analyze application-based E-assessment models and their utilization in school guidance and counseling services. The study employed a Systematic Literature Review (SLR) method guided by PRISMA 2020. Data were obtained from national and international scientific articles published between 2016 and 2026 through Google Scholar, DOAJ, ERIC, and ResearchGate. The findings indicate that commonly used applications include Google Forms, Quizizz, Kahoot, Moodle, and Aku Pintar. Google Forms is used for needs assessments and evaluation of counseling services, while Quizizz and Kahoot increase students’ motivation and participation through interactive assessments. Moodle functions as an LMS-based assessment system, whereas Aku Pintar is utilized for assessing students’ interests, talents, and career planning. The study concludes that application-based E-assessment improves the effectiveness, efficiency, flexibility, and accuracy of digital data-based guidance and counseling services.